Right to Sexual Autonomy of Children—Implications of the UNCRC upon the Indian Law on the Age of Consent - Lina Acca Mathew (International Journal for Crime, Justice and Social Democracy, 2019)
This article discusses the implications of sexual autonomy of children under international child rights regime upon Indian law. Indian general criminal law defining the offence of rape and a special statute defining different types of child sexual assault led to the inference that the current age of consent is 18 years. Despite statutory prohibition of child marriages in India, the general criminal law contains an explanatory provision exempting the rape of a married woman above the age of 15. The Supreme Court of India struck this down as discriminatory and inconsistent with existing provisions of law, increasing the age of consent of a married woman to 18. It is necessary for Indian law to clearly define the age of consent of children, and grant rights of sexual autonomy to children who are capable of making their own decisions, without compromising on penalising sexual offenders of children.